Answer:
3p^3 + qp^2 - pq^2 + 3q^3
Step-by-step explanation:
(p²-pq + q²) ( 3p+ 3q)
3p^3 + 3qp^2 - 3qp^2 - 3pq^2 + 3pq^2 + 3q^3
3p^3 + qp^2 - pq^2 + 3q^3
Answer:
eli
Step-by-step explanation:
The transformation of <span>f(x)=15tanx would be achieved by dilating y</span>=tanx graph 15 times. This transformation will cause y'=15 y. This will increase the value of dilation become 15 times of the original
The transformation of g(x)=15tanx would be achieved by shifting y=tanx graph 15 right. This transformation will cause x'=x+15. This will change the value from tan x into tan(x+15)